Analisis Efisiensi dan Efektivitas Pengelolaan Anggaran - Ardin Umar; Jamiludin Hasan; Saiful Tanimbar (Peneliti.net, 2021)
The results revealed that the efficiency ratio analysis results showed an average efficiency in managing the Morotai Island Regional Disaster Management Agency's budget management from 2017 to 2019 of 1.16%. Thus, it can be concluded that efficient budget management has been implemented. The effectiveness ratio analysis results showed the average effectiveness of budget management of the Morotai Island Regional Disaster Management Agency from 2017 to 2019 was 97.27%, meaning that budget management was applied